Strategi Komunikasi Persuasif Difabel Slawi Mandiri (DSM) Dalam Membangun Kepercayaan Diri Orang Yang Pernah Mengalami Kusta (OYPMK) di Kabupaten Tegal - Ike Desi Florina; Choirunnisa Adinda Prihatin; Inas Sany Muyassaroh (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Leprosy cases in Central Java Province in 2022 will reach 2,263 leprosy cases, with Tegal Regency ranking second with a total of 12% of the total cases. The stigma that is still attached to people who have had leprosy (OYPMK) in Tegal Regency has a significant psychological impact, hindering social interaction. Through interviews with Disabled Slawi Mandiri (DSM), their strategies were revealed, such as home visits, socialization, peer counseling for people who have experienced leprosy (OYPMK). This research uses a qualitative approach, analyzing the communication strategies of Disabled Slawi Mandiri (DSM). ) through interviews and case studies. The results of this research show three strategies: psychodynamics, sociocultural persuasion, and the meaning construction. Each strategy aims to change people's perceptions, provide support, and increase understanding about leprosy, as well as increase the self-confidence of people who have experienced leprosy (OYPMK). The research conclusions show that the persuasive communication strategies of Disabled Slawi Mandiri (DSM) can be grouped into three types, namely psychodynamics, sociocultural persuasion, and the meaning construction. The aim is to provide understanding, support behavior change, and increase the self-confidence of people who have experienced leprosy (OYPMK), as well as reduce stigma in society.